Historical maps and geopolitics: in the context of indigenous culture, state interests and borders conflict (Journal of Geography and Environmental Management, 2024)
The article discusses a scientific definition, function, and history of the emergence of geographical maps and their importance in the history of human development. Information is provided about the oldest maps of the Earth currently found, about the cities and countries in which they were created. The art of mapping in ancient Egypt, the map of Chatalhoyuk in Mesopotamia, the latest scientific research on it, and the map of the Babylonian world are also described, as well as the meaning of its objects. It provides an overview of the history of the ancient Middle East. An overview of the contributions of ancient Greek philosophers in the history of cartography, and did a comparative analysis  of the Anaximander, Eratosthenes, Strabo, Ptolemy, and ancient Roman maps.In the article, the authors  examines the importance of the map "Al-Mamun" during the time of the caliph Al-Mamun and the map "Image of the Earth" by Al-Idrisi, which are examples of the cartographic development that came with the Islamic civilisation. Many historical names of the Caspian Sea are explained based on the Al-Idrisi map.A unique map due to our historical statehood is the map of Abraham Ortelius. This map is comprehensively considered in the article. Brief descriptions of the way of life, economy and culture of Tumens, Kazakhs, Nogais and Muslim Turks on the map have been translated into Kazakh. Especially on the map, the inscription of the country "Cassakia" in the region called "Tartaria", where the Turkic peoples lived at that time, is emphasized as a historical and scientific proof of the continuous statehood of Kazakhstan. The influence of historical maps on modern geopolitics is demonstrated by the example of Israel and Palestine.